Concept mapping sociocultural aspects of cervical cancer prevention among African American women - Carmack, Chakema; Roncancio, Angelica; Coleman, Taylor M.; McKay, Sarah (Frontiers in Public Health, 2024)
For African American women in Houston, cervical cancer mortality is disproportionate to their racial and ethnic counterparts. Most notably, lack of human papillomavirus (HPV) screening, vaccination, and later diagnosis increase cervical cancer mortality. However, cervical cancer is largely preventable. While previous research has identified a few social determinants that are specifically related to cervical cancer (e.g., education, income, neighborhood), there may be a host of additional social and cultural factors that contribute to a lack of preventative behavior. The present study used concept mapping to explore sociocultural determinants of cervical cancer prevention beliefs among young African American women. N=15 African American women, ages 18-25, participated in a group concept mapping session focused on cervical cancer knowledge, beliefs about women's health, and how their social environment and culture plays a role in their conceptualization of cervical cancer prevention. Five overarching concepts emerged: 1) Screening, 2) Support System, 3) Cervical Cancer 101 (knowledge), 4) Fatalism, and 5) Ease of Prevention. The present study highlights the use of concept mapping for prevention science, particularly for understanding cervical cancer screening barriers, avenues for intervention, and public health messaging. We discuss the findings and implications for public health research in cervical cancer prevention tailored for African American women.